FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN INVESTASI PROPERTI PADA KOTA BATAM - Hesniati; Dedy (LPPM Universitas Sains dan Teknologi Komputer, 2021)
The behavior of investment decisions began to attract the attention of academics internationally. This study was conducted to investigate the effect of behavioral finance by applied variable overconfidence, representativeness, mental accounting, loss aversion and herding on investment decisions. The total sample collected and used in the study amounted to 203 respondents in Batam City and analyze using multiple linear regression method. The result showed that overconfidence, mental accounting, and herding have a significant positive effect on investment decisions, while the representativeness and loss aversion variables doesn’t affect investment decisions.